1996
DOI: 10.1002/(sici)1097-4695(199604)29:4<517::aid-neu8>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve-dependent changes in adult frog tectal cell phenotypes

Abstract: Optic nerve activity helps determine the placement of retinal ganglion cell terminals in the optic tectum of the frog. We investigated whether the presence of this nerve might also influence a characteristic of its target structure, neurotransmitter biosynthesis. We performed unilateral optic nerve transections on adult animals and assayed the percent and intensity of substance P‐ and serotoninlike immunoreactive (SP‐ir and 5‐HT‐ir, respectively) cells in the deafferented and afferented tectal lobes. Regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Consistent with the idea that this cholinergic pathway is activated by glutamatergic depolarization of tectal cells is the observation that chronically blocking tectal non-NMDA receptors with CNQX produces a decrease in SP-ir cells in the untreated lobe. This decrease mimics that seen in the afferented lobe in response to optic nerve transection (Liu and Debski, 1996).…”
Section: The Regulation Of Sp Expression In the Developing Optic Tectumsupporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with the idea that this cholinergic pathway is activated by glutamatergic depolarization of tectal cells is the observation that chronically blocking tectal non-NMDA receptors with CNQX produces a decrease in SP-ir cells in the untreated lobe. This decrease mimics that seen in the afferented lobe in response to optic nerve transection (Liu and Debski, 1996).…”
Section: The Regulation Of Sp Expression In the Developing Optic Tectumsupporting
confidence: 71%
“…The size of this population is dependent on the presence of the optic nerve. Unilateral optic nerve transection causes a decrease in SP-ir tectal cells in both the adult and developing systems, but in the former instance this decrease occurs in the afferented tectal lobe (Liu and Debski, 1996), while in the latter it happens in the deafferented lobe (Tu and Debski, 1999). Although direct optic nerve input to each tectal lobe originates almost entirely from the contralateral retina (Singman and Scalia, 1990), pathways exist within the brain that relay information from one tectal lobe to the other (Gruberg and Udin, 1978;Grobstein and Comer, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrated that transection of the optic nerve causes a decrease in SP-IR cells in the innervated tectal lobe, whereas SP expression in the deafferented lobe is unaffected (Liu and Debski, 1996). Because each tectal lobe receives direct retinal input almost exclusively from the contralateral eye (Singman and Scalia, 1990), this result suggested to us that SP expression was being regulated by activity that was relayed between the two tectal lobes.…”
Section: Sp Expression Is Regulated By Activity Originating From the mentioning
confidence: 87%
“…SP is expressed in a subpopulation of tectal neurons found exclusively in layer 6 ( Kuljis and Karten, 1982). Our previous work has shown that unilateral optic nerve transection decreases the percentage of SP-IR cells in the afferented tectum but leaves the deafferented tectum unchanged (Liu and Debski, 1996). This suggests that SP expression in tectal cells is regulated by activity that is relayed from one tectal lobe to the other.…”
Section: Sp Expression Is Regulated By Non-nmda Glutamate Receptor Acmentioning
confidence: 99%
See 1 more Smart Citation